Strategies for Social Networks Modeling - Amato, Flora; Barolli, Leonard; Moscato, Vincenzo; Picariello, Antonio; Sperli, Giancarlo (2018 32nd International Conference on Advanced Information Networking and Applications Workshops (WAINA), 2018)
Nowadays, Social Network Analysis is considered a hot research topic. In this paper, we propose a novel data model for Multimedia Social Networks, i.e. particular social media networks that combine information on users belonging to one or more social communities together with the multimedia content that is generated and used within the related environments. The proposed model relies on the hypergraph data structure to capture and represent in a simple way all the different kinds of relationships that are typical of social media networks, and in particular among multimedia contents, users and multimedia content and users themselves.